Kajian Psikologis Mengenai Kesadaran Kesehatan Mental pada Serial “Daily Dose of Sunshine” : (Analisis Gangguan Mental) - Aisyatin Kamila; Finanin Nur Indana (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
This article aims to explore the psychological values presented in the series Daily Dose of Sunshine. Released in 2023, this medical-themed series addresses mental health issues and portrays the emotional and psychological journeys of its characters. As a series that highlights mental health, it plays a significant role in raising awareness and understanding of mental health problems. The objective of this study is to examine how the series represents psychological concepts related to mental health through the depiction of various psychological disorders. The method employed in this research is descriptive qualitative. This approach is used to observe and describe data found in the Daily Dose of Sunshine series. The data analyzed includes dialogues between characters and scenes containing psychological values. The findings indicate that the series presents several types of mental disorders, such as bipolar disorder, anxiety disorder, delusions, schizophrenia, dissociative amnesia, borderline personality disorder (BPD), pseudodementia, obsessive-compulsive disorder (OCD), post-traumatic stress disorder (PTSD), and depression. These disorders are conveyed through dialogues and textual elements within scenes that depict each specific mental illness. Moreover, the series also illustrates other mental health issues such as insomnia, gaslighting, self-harm, and panic attacks.